The relationship between stock market development and macroeconomic fundamentals in the Visegrad Group - Tomáš Pražák; Daniel Stavárek (Comparative Economic Research. Central and Eastern Europe, 2017)
This study examines the effect of specific macroeconomic factors on the stock prices of selected financial sector companies listed on the Central European Exchanges (Budapest Stock Exchange, Prague Stock Exchange, Bratislava Stock Exchange, or Warsaw Stock Exchange). We investigate the nature of the causal relationships between macroeconomic factors and stock prices. The long-term causality, tested using the Johansen cointegration test, and the short-run dynamics between the variables, examined using the VECM model, are explored using quarterly data from the 2005-2014 period. The short-term causality shows the possibility of time series fluctuations; however a steady state should be achieved in the long-term. In general, we confirmed that macroeconomic fundamentals had a negative impact on stock prices. The interest rate, which also has a negative impact, is the most prominent predictor of the long-run developments. We also found very rare examples of macroeconomic variables that explain changes in stock prices within the VECM framework.
Keywords: E02; G15; G21; 330; stock prices; macroeconomic fundamentals; Visegrad Group; causality; VECM